Connecting During COVID-19: A Protocol of a Volunteer-Based Telehealth Program for Supporting Older Adults' Health - Dikaios, Elena; Sekhon, Harmehr; Allard, Alexandre; Vacaflor, Blanca; Goodman, Allana; Dwyer, Emmett; Lavin-Gonzalez, Paola; Mahdanian, Artin; Park, Haley; Walsh, Chesley; Sasi, Neeti; Nazar, Rim; et al. (Frontiers in Psychiatry, 2020)
Introduction: Social-distancing due to COVID-19 has led to social isolation, stress, and mental health issues in older adults, while overwhelming healthcare systems worldwide. Telehealth involving phone calls by trained volunteers is understudied and may be a low-cost, scalable, and valuable preventive tool for mental health. In this context, from patient participatory volunteer initiatives, we have adapted and developed an innovative volunteer-based telehealth intervention program for older adults (TIP-OA). Methods and analysis: To evaluate TIP-OA, we are conducting a mixed-methods longitudinal observational study. Participants: TIP-OA clients are older adults (age ≥ 60) recruited in Montreal, Quebec. Intervention: TIP-OA volunteers make weekly friendly phone calls to seniors to check in, form connections, provide information about COVID-19, and connect clients to community resources as needed. Measurements: Perceived stress, fear surrounding COVID-19, depression, and anxiety will be assessed at baseline, and at 4- and 8-weeks. Semi-structured interviews and focus groups will be conducted to assess the experiences of clients, volunteers, and stakeholders. Results: As of October 15th, 2020, 150 volunteers have been trained to provide TIP-OA to 305 older clients. We will consecutively select 200 clients receiving TIP-OA for quantitative data collection, plus 16 volunteers and 8 clinicians for focus groups, and 15 volunteers, 10 stakeholders, and 25 clients for semi-structured interviews. Discussion: During COVID-19, healthcare professionals’ decreased availability and increased needs related to geriatric mental health are expected. If successful and scalable, volunteer-based TIP-OA may help prevent and improve mental health concerns, improve community participation, and decrease healthcare utilization.